Moderating Role of Profitability in The Association Between Green Accounting and Firm Value - Raldin Alif Al Hazmi; Ammar Ramadhan; Amrie Firmansyah (Journal of Governance Risk Management Compliance and Sustainability, 2024)
Environmental pollution often occurs in various parts of the world, including Indonesia. Indonesia, with abundant natural resources, raises new environmental issues. Companies in the mining and coal sector cause significant environmental damage in Indonesia. Not infrequently, these companies are less aware of the importance of preserving the environment. Most companies only think about profit without paying attention to environmental sustainability. This study aims to analyze and determine the effect of green accounting implementation on firm value and profitability on moderating the interaction between green accounting and firm value. This study uses data from 14 companies engaged in mining and coal for 2020-2022 on the Indonesia Stock Exchange (IDX) website and the Proper Value Index issued by the Decree of the Ministry of Environment with a sample of 42 sample data. The test was conducted using panel data multiple linear regression analysis. This study concludes that green accounting affect firm value. Profitability has not been able to model the interaction between green accounting and firm value. This study is expected to add to the literature on financial accounting, sustainability accounting, and green accounting, especially regarding firm value and investor reaction. This research is also expected to provide attention to companies in Indonesia to improve their green sustainability. There is a need to increase the role of the government in overseeing the implementation of green accounting in companies to ensure the sustainability of the Indonesian environment.